Development of a machine learning‐based predictive model for prediction of success or failure of medical management for benign prostatic hyperplasia. Issue 4 (24th February 2023) - Pham, Kyle; Ray, Al W.; Fernstrum, Austin J.; Alfahmy, Anood; Ray, Soumya; Hijaz, Adonis K.; Ju, Mingxuan; Sheyn, David
Abstract: Objective: To develop a novel predictive model for identifying patients who will and will not respond to the medical management of benign prostatic hyperplasia (BPH). Methods: Using data from the Medical Therapy of Prostatic Symptoms (MTOPS) study, several models were constructed using an initial data set of 2172 patients with BPH who were treated with doxazosin (Group 1), finasteride (Group 2), and combination therapy (Group 3). K‐fold stratified cross‐validation was performed on each group, Within each group, feature selection and dimensionality reduction using nonnegative matrix factorization (NMF) were performed based on the training data, before several machine learning algorithms were tested; the most accurate models, boosted support vector machines (SVMs), being selected for further refinement. The area under the receiver operating curve (AUC) was calculated and used to determine the optimal operating points. Patients were classified as treatment failures or responders, based on whether they fell below or above the AUC threshold for each group and for the whole data set. Results: For the entire cohort, the AUC for the boosted SVM model was 0.698. For patients in Group 1, the AUC was 0.729, for Group 2, the AUC was 0.719, and for Group 3, the AUC was 0.698. Conclusion: Using MTOPS data, we were able to develop a prediction model with an acceptable rate of discrimination of medical management success for BPH.